2020
DOI: 10.1021/jacs.0c01830
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Origin of Stereoselectivity in an Asymmetric Chlorolactonization Catalyzed by (DHQD)2PHAL

Abstract: Electrophilic halofunctionalization reactions have undergone a resurgence sparked by recent discoveries in the field of catalytic asymmetric halocyclizations. To build mechanistic understanding of these asymmetric transformations, a toolbox of analytical methods has been deployed, addressing the roles of catalyst, electrophile (halenium donor), and nucleophile in determining rates and stereopreferences. The test reaction, (DHQD)2PHAL-catalyzed chlorocyclization of 4-arylpent-4-enoic acid with 1,3-dichloro-5,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 69 publications
3
29
0
Order By: Relevance
“…43,44 State-of-theart research, oen uses an integrated computational and experimental approach to gain such knowledge, as exemplied by the collaborative works of Jackson and Borhan. [37][38][39] On the computational side, static DFT calculations are routinely used, due to the availability of several user friendly soware, limited hardware requirements and the extensive development of this approach. [45][46][47] Most static DFT calculations simplify solvation effects by implicit solvation models, negating the possibility of observing explicit interactions between the solvent and reactants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 State-of-theart research, oen uses an integrated computational and experimental approach to gain such knowledge, as exemplied by the collaborative works of Jackson and Borhan. [37][38][39] On the computational side, static DFT calculations are routinely used, due to the availability of several user friendly soware, limited hardware requirements and the extensive development of this approach. [45][46][47] Most static DFT calculations simplify solvation effects by implicit solvation models, negating the possibility of observing explicit interactions between the solvent and reactants.…”
Section: Introductionmentioning
confidence: 99%
“…Only very recently, the mechanistic aspects of the (DHQD) 2 PHAL catalysed asymmetric chlorolactonization reaction were unveiled by a joint effort by Jackson and Borhan. 37 Kinetic studies were performed to establish that the reaction shows a first order dependence on both the catalyst and the halogen source. Furthermore, ROESY NMR spectroscopy and static DFT calculations provided a resting state complex and plausible transition states for the catalytic cycle.…”
Section: Introductionmentioning
confidence: 99%
“…As depicted in the cocrystal structure of 1a –(DHQ) 2 PHAL (Scheme ), substrate 1a binds to the basic quinuclidine moiety to give an 1:2 base–acid adduct. This observation is in alignment with a recent study of Borhan and co-workers, in which a substrate–catalyst adduct was verified by NMR and computational studies . In addition, an NMR study of (DHQ) 2 PHAL and NBS suggested that one of the catalyst’s quinuclidine moieties might generate an N -Br species .…”
mentioning
confidence: 99%
“… 14 There is also evidence that protonation of cinchona alkaloid dimeric catalysts could lead to altered conformations. 15 An early screening of solvents showed that the addition of 1,1,1,3,3,3-hexafluoroisopropanol (HFIP, entries 2 and 3, Table 1 ) improved the enantiomeric excess of 2a , while tremendously increasing the rate of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…14 There is also evidence that protonation of cinchona alkaloid dimeric catalysts could lead to altered conformations. 15 An early screening of solvents showed that the addition of 1,1,1,3,3,3,-hexafluoroisopropanol (HFIP, entries 2-3, Table 1) improved the enantiomeric excess of 2a, while tremendously increasing the rate of the reaction. DCDMH proved to be the optimal chlorenium source as the less active NCS (entry 5) was sluggish and gave slightly lower ee, while the more active chlorenium TCCA (entry 6) gave a lower yield.…”
Section: Ritter-type Exploratory Investigationsmentioning
confidence: 99%